The scarlet letter : retold classic novel - Hawthorne, Nathaniel, 1804-1864. (Logan, Iowa : Perfection Learning, 1992)
In early colonial Massachusetts, a young woman endures the consequences of her sin of adultery and spends the rest of her life in atonement.
Keywords: Puritans -- Massachusetts -- Juvenile fiction; Puritans -- Fiction; Massachusetts -- History -- Colonial period, ca. 1600-1775 -- Juvenile fiction; Massachusetts -- History -- Colonial period, ca. 1600-1775 -- Fiction